Studi Kepustakaan Mengenai Tantangan Pengembangan Smart Tourism di Bandung, Jawa Barat - Alfiani, Shifa Regitha; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p07, 2023)
This study aims to determine the challenges found in the process of developing smart tourism in the city of Bandung so that it can be used as a reference in developing strategies for developing smart tourism in other cities. Smart Tourism is dynamic because it moves hand in hand with the Information and Communication Technology (ICT) revolution. It is the existence of ICT that encourages the tourism sector to be "smarter" in improving the quality of its performance and services. This study uses a qualitative descriptive research method with a literature approach from previous research that raises relevant topics; smart tourism Bandung. The data was analyzed from several articles from Research Gate and Google Scholar which had previously gone through a filtering process with several features. The results of the study show that apart from obtaining many benefits, the development of smart tourism in the city of Bandung also faces many challenges. Among them are communication and linkages between stakeholders, the application of sustainable technology, marketing destinations, to facilities and infrastructure supporting tourism activities Keywords: Smart tourism, Bandung, Challenge, Research Study